Assessment of dynamic contact of the bent part of the drill string with the wall of the directed well - Gridzhuk, Jaroslav; Slabyi, Orest; Kondur, Taras (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
Taking into account the specifics of the stress-strain state of the bent part of the drill string pressed against the well wall, as well as the geometry of their mutual spatial arrangement, the analytical method of determining the area of ​​their contact forses zone is substantiated. З урахуванням особливостей напружено-деформованого стану прогнутої ділянки бурильної колони, притиснутої до стінки свердловини, а також геометрії їх взаємного просторового розташування, обґрунтовано аналітичний спосіб визначення контактних сил.